2017
DOI: 10.1038/s41467-017-00688-0
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglial excitability mediated by glutamatergic inputs and Nav1.2 activation

Abstract: Oligodendrocyte (OL) maturation and axon-glial communication are required for proper myelination in the developing brain. However, physiological properties of OLs remain largely uncharacterized in different brain regions. The roles of oligodendroglial voltage-activated Na+ channels (Nav) and electrical excitability in relation to maturation to the myelinating stage are controversial, although oligodendroglial excitability is potentially important for promoting axon myelination. Here we show spiking properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 43 publications
5
65
0
Order By: Relevance
“…In whole‐cell voltage‐clamp recordings, these GCaMP6f + cells displayed outwardly rectifying K + currents and, and 37.5% of cells showed transient inward Na + currents (Figure e). This electrophysiological profile aligns with what has previously been observed in pre‐myelinating OLs in the MNTB (Berret et al, ).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In whole‐cell voltage‐clamp recordings, these GCaMP6f + cells displayed outwardly rectifying K + currents and, and 37.5% of cells showed transient inward Na + currents (Figure e). This electrophysiological profile aligns with what has previously been observed in pre‐myelinating OLs in the MNTB (Berret et al, ).…”
Section: Resultssupporting
confidence: 90%
“…How do Ca 2+ ‐impermeable AMPAR currents contribute to Ca 2+ responses in OLs? Our previous study showed that glutamatergic input depolarized pre‐myelinating OLs and consequently activated voltage‐gated ion channels (Berret et al, ). We examined whether Ca 2+ influx via Ca v channels could be a source of glutamate‐induced Ca 2+ rise in OLs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations